Analysis of provisions of Law on free legal aid regulating free legal aid in cross-border dispute de lege lata and de lege ferenda - Stanković, Sanja (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Right on legal aid in cross-border dispute is a procedural right of the person who has the citizenship, domicile or habitual residence on the territory of one state to accomplish the right on legal aid in dispute which is conducted before the competent authority of other state. Right on free legal aid in cross-border dispute in Republic of Serbia is regulated by the Law on free Legal Aid. The Law on free Legal Aid regulates the exercise of the right on free legal aid in territory of European Union, e.g. definition of cross-border dispute, the types of free legal aid, the conditions with which the free legal aid's applicant should fulfill in order to be granted the status of user, the free legal aid procedure when the dispute with the international element is conducted before the court in territory of Serbia or other Member States of the European Union, and the types of costs accompanied by free legal aid. Legal aid applicant which has the domicile or habitual residence in the Member State of European Union territory, in order to exercise the right on free legal aid in dispute which is conducted before the court of other Member State of the European Union, submits the free legal aid application in two ways: direct to the receiving authority of state in which dispute is conducted or indirect through transmitting authority in which the applicant has the domicile or habitual residence. In Republic of Serbia the transmitting and receiving authority is the Ministry of Justice. When the cross-border dispute is conducted before the competent court in the territory of the Republic of Serbia, Ministry of Justice is competent for deceding about the applicant legal aid application.